CNS Structural Anomalies in Iranian Children with Global Developmental Delay - ZAMANI, Gholam Reza; SHERVIN-BADV, Reza; NIKSIRAT, Ali; ALIZADEH, Houman (Iranian Journal of Child Neurology, 2013)
How to Cite This Article: Zamani GH, Shervin Badv R, Niksirat A, Alizadeh H. CNS Structural Anomalies in Iranian Children with Global Developmental Delay. Iran J Child Neurol. 2013 Winter; 7 (1):25-28. Objective Central Nervous system (CNS) malformations are one of the most important causes of global developmental delay (GDD) in Children. About one percent of infants with GDD have an inherited metabolic disorder and 3-10 percent have a chromosomal disorder. This study aimed to survey the frequency of brain structural anomalies and their subtypes among the variety of etiologic factors in children with GDD in our patients. Materials & Methods This study used the results of neuroimaging studies [unenhanced brain Magnetic Resonance Imaging (MRI)] of all children who had been referred for evaluation of GDD to outpatient Clinic of Pediatric neurology at Children’s Medical Center affiliated to Tehran University of Medical Science between September 2009 and September 2010. Results In this study, unenhanced brain MRI was performed on 405 children, of which 80 cases (20 percent) had brain structural anomalies. In 8.7 percent of the cases, previous history of brain structural disorders existed in other children of the family and 20 percent of mothers had inadequate consumption of folate during pregnancy. Conclusion Based on the results of this study, unenhanced cranial MRI seems to be a fundamental part of evaluation in all children with GDD. Adequate folate consumption as prophylaxis as well as genetic counseling can be worthy for high-risk mothers who have previous history of CNS anomaly or miscarriage to avoid repeated CNS anomalies in their next pregnancies. References 1. Fenichel M. Clinical Pediatric Neurology: A Signs and Symptoms Approach. 6th ed. Philadelphia: Saunders; 2009. p. 119-52. 2. A guide to investigation of children with developmental delay in East Anglia 2005Available from:http://www. phgfoundation.org/file/2366. 3. Williams J. Global developmental delay–globally helpful? Dev Med Child Neurol 2010;52(3):227. 4. Shevell M, Ashwal S, Donley D, Flint J, Gingold M, Hirtz D, et al. Practice parameter: Evaluation of the child with global developmental delay: Report of the Quality Standards Subcommittee of the American Academy of Neurology and The Practice Committee of the Child Neurology Society. Neurology 2003;60(3):367-80. 5. Whiting K. Investigating the child with learning difficulty.Current Pediatrics 2001;11(4):240-7. 6. Aicardi J. The etiology of developmental delay. Semin Pediatr Neurol 1998;5(1):15-20. 7. Von Wendt L, Rantakallio P. Congenital malformations of the central nervous system in a 1-year birth cohort followed to the age of 14 years. Childs Nerv Syst.1986;2(2):80-2. 8. Kuzniecky R, Murro A, King D, Morawetz R, Smith J, Powers R, et al. Magnetic resonance imaging in childhood intractable partial epilepsy: Pathologic correlations. Neurology1993;43:681-7. 9. Massimi L, Paternoster G, Fasano T, et al: On the changing epidemiology of hydrocephalus. Childs Nerv Syst. 2009;25(7):795-800. 10. Warkany J, Lemire RJ, Cohen Jr MM. Mental retardation and congenital malformations of the central nervous system. Chicago: Year Book Medical Publishers; 1981. 11. Petrini J, Damus K, Johnston RB Jr. An overview of infant mortality and birth defects in the United States. Teratology. 1997;56(1-2):8-10. 12. Rosano A, Botto LD, Botting B, Mastroiacovo P. Infant mortality and congenital anomalies from 1950 to 1994: an international perspective. J Epidemiol Community Health 2000; 54(9):660-6. 13. Cordero JF. Finding the causes of birth defects. The New England Journal of Medicine. 1994;331(1):48-9. 14. Srour M, Mazer B, Shevell MI. Analysis of Clinical Features Predicting Etiologic Yield in the Assessment of Global Developmental Delay.Pediatrics 2006 ;118(1):139-45. 15. Meral O, Burak T, Nur A. Etiologic evaluation in 247 children with GDD at Istanbul, Turkey. J Trop Pediatr 2005;51(5):310-3. 16. World Health Organization. Weekly Iron-Folic Acid Supplementation (WIFS) in women of reproductive age: its role in promoting optimal maternal and child health. Geneva, World Health Organization, 2009. WHO/NMH/ NHD/MNM/09.2. p. 2.